Study for Structure Analysis for Different Material Use for VTOL Drone - sallehuddin, asma'i arif (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This project research was focusing on making the structure analysis for different material that can be use for VTOL drone. In this research there are five different configuration of material use for VTOL drone. The best material will be chose. The study involved analyzing the 3D model of the base design of VTOL drone to understand its components, connectors and other elements. static analysis was conducted on the respective assemblies to observe the strain, displacement, and von Mises stress experienced by the wings and quad arms during the drone hovering. The research methodology employs with designing the 3D VTOL drone and static simulation. Subsequently, the results that been obtained are carefully evaluated. The simulation findings that selecting the material give different effect on VTOL drone during hovering.